PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF NHT DAN JIGSAW TERHADAP PENGUASAAN MATERI SEKS BEBAS - Danil Endarto; Surisman Surisman; Akor Sitepu (JUPE (Jurnal Penjaskesrek), 2013)
Of thie research to find the comparation of learning cooperative of NHT type and jigsaw type toward the mastery of free sex material at eight grade students of SMP IT Fitrah Insani Bandar Lampung in 2010/2011 This research used comparative method. This research was conducted for 1.5 month at SMP IT Fitrah Insani Bandar lampung. Subject of this research was 20 students of eight grade. Data technique of this research used pre test and post test. The pre test and post test analysis used uji t analysis technique. Result of the research from the uji t accounting student’s learning result comparison was thitung : 0.440 ttabel = 1.734, it mean that was significant difference of learning result from whose tought by NHT type and Jigsaw type. From the research it could be conclude that learning result of cooperative learning of NHT type was better than Jigsaw type at eight grade student of SMP IT Fitrah Insani Bandar lampung in 2011/2012.Kata kunci : pembelajaran NHT, pembelajaran jigsaw, materi seks bebas